Gastrointestinal nematode infection in beef cattle of different genetic groups in Brazil - Oliveira, M. C. S.; Alencar, M. M.; Chagas, A. C. S.; Giglioti, R. [UNESP]; Oliveira, Henrique Nunes de [UNESP] (Elsevier B.V., 2009)
Resistance to natural infection by gastrointestinal nematodes was compared in 67 female calves of the following genetic groups: Nelore (NX); 1/2 Senepol + 1/2 Nelore (SN); and 1/2 Aberdeen Angus + 1/2 Nelore (AN). The NX (n = 26), SN (n = 23) and AN (n = 18) animals were monitored for 14 months, during which they remained without treatment, allowed to graze in a tropical environment. Eggs per gram of feces (EPG), coprocultures and packed cell volume (PCV) were carried out monthly. No significant effects of the interaction between the genetic groups and month/year of collection and the genetic group on the EPG were found, but there was a significant influence of the month of collection (P < 0.01). The monthly PCV measurements did not differ for the animals of the three genetic groups and there was no association found between the EPG and PCV. The animals of the SN and NX groups showed similar numbers of EPG with results zero, while for the AN group these numbers were significantly lower (P < 0.05). Although the NX group had a large number of EPG with results zero, it also contained many animals with high counts, meaning this group had higher averages during the entire study period. The following nematode genera were found in the coprocultures: Haemonchus, Cooperia, Oesophagostomum and Trichostrongylus, the latter in smallest proportion. There was no significant difference between the genetic groups for averages of all parasites identified, except Cooperia, which were present in higher numbers in the animals of the NX group (P < 0.05). The results obtained in this experiment suggest that the use of Bos taurus x Bos indicus crossbreeds can be a good strategy to reduce the use of chemical control in Brazil. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cattle; Nematode; Genetic susceptibility